1987
DOI: 10.2466/pms.1987.64.3c.1243
|View full text |Cite
|
Sign up to set email alerts
|

Some Attractiveness Parameters from Birth to Four Years

Abstract: Facial drawings of infants from 2 wk. to 4 yr. varying in eye height, pupil size, and mouth shape were rated for attractiveness by 181 female and 82 male undergraduates. Stimulus age was the most influential determinant of attractiveness. None of the facial variables showed a consistent effect at all ages though eye height was influential at 1 yr. and older. Judged in the context of a substantial age range the very young seem less attractive in absolute terms and possibly less susceptible to discriminations of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
8
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 5 publications
1
8
0
Order By: Relevance
“…In the studies reported here, we investigated the influence of eye size. Adults rate drawings or photographs of faces with larger eyes as more attractive than faces with smaller eyes, and this is true across faces of different age (ie infants, adults), sex, and race (Horvath et al 1987;Keating 1985;Apatow 1983^1984;McArthur and Berry 1987;Sternglanz et al 1977). Adults' preferences for larger eyes may reflect their more general preference for`babyish' faces (Hildebrandt and Fitzgerald 1979;Apatow 1983^1984;Maier et al 1984)öin this case for faces with larger eye height and width in relation to a smaller head frame, and for expressive faces (Cunningham 1986;Cunningham et al 1995)öin this case for faces with wider pupils and larger eye height (as occurs with the raised eyelids of expressive faces).…”
mentioning
confidence: 99%
“…In the studies reported here, we investigated the influence of eye size. Adults rate drawings or photographs of faces with larger eyes as more attractive than faces with smaller eyes, and this is true across faces of different age (ie infants, adults), sex, and race (Horvath et al 1987;Keating 1985;Apatow 1983^1984;McArthur and Berry 1987;Sternglanz et al 1977). Adults' preferences for larger eyes may reflect their more general preference for`babyish' faces (Hildebrandt and Fitzgerald 1979;Apatow 1983^1984;Maier et al 1984)öin this case for faces with larger eye height and width in relation to a smaller head frame, and for expressive faces (Cunningham 1986;Cunningham et al 1995)öin this case for faces with wider pupils and larger eye height (as occurs with the raised eyelids of expressive faces).…”
mentioning
confidence: 99%
“…For over half a century, ethologists (Lorenz, 1943), psychiatrists (Bowlby, 1982), and psychologists (Hildebrandt & Fitzgerald, 1979;Horvath, Szmigelsky, & Fenton, 1987;Sternglanz, Gray, & Murakami, 1977) have suggested that infant faces might influence cognitive processes associated with parental care. Indeed, an infant's attractiveness may predict maternal behaviors and attitudes towards that infant (Langlois, Ritter, Casey, & Sawin, 1995).…”
mentioning
confidence: 99%
“…Male nonparents were less punitive than female nonparents, but male parents were more punitive than female parents. Although Horvath, et al (1987) suggested that very young children may be less susceptible to attractiveness distinctions, it is nonetheless clear that attractiveness is a meaningful stimulus characteristic of children (Kenealy, et al, 1987;Alley, 1981;Hildebrandt & Fitzgerald, 1979;Kirkland & Smith, 1978;Sternglanz, et al, 1977). When the data were analyzed separately for the two stimulus ages (leaving the independent variables of attractiveness, sex, subjects' parenthood, and subjects' sex), no main or interaction effects occurred for the 2-yr.-old children.…”
Section: Methodsmentioning
confidence: 92%
“…A facial line drawing of "Pat," occupying an area approximately 10 by 10 cm, was placed in the upper right corner of the sheet. The drawings were taken from Horvath, et al (1987) and depicted 2-and 4-yr.-old children of both sexes: at each age/sex combination two drawings representing relatively attractive and unattractive facial feature combinations were used. In all subject groups both attractive and unattractive faces for a given age/sex combination were tested to avoid confounding by class membership.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation